Religion, religious ethics, and nursing - Fowler, Marsha Diane Mary (Springer, 2012)
"The Reverend Dr. Marsha Fowler and her colleagues have written a landmark book that will change and enlighten the discourse on religion and spirituality in nursing. The authors address the awkward silence on religion in nursing theory and education and with insightful scholarship move beyond the current level of knowledge and limited discourse on religion in nursing theory, education and practice. This book is path-breaking in that [it] gives many new ways to think about the relationships between ethics, health, caregiving, moral imagination, religion and spirituality.". From the Foreword by.